A new algorithm of treatment choice in primary open-angle glaucoma - A. A. Antonov; I. V. Kozlova; A. A. Vitkov; T. M. Agadzhanyan (Российский офтальмологический журнал)
Purpose: to develop a comprehensive algorithm for choosing the optimal method for monitoring and treating patients with primary openangle glaucoma (POAG). Material and methods. 30 patients with POAG, aged 30 to 86, underwent an ophthalmological examination which included visometry, standard automatic perimetry, tonometry, ophthalmoscopy, and biomicroscopy. The data obtained were evaluated on a point scale according to the innovative algorithm, on the basis of which a plan of patient management was recommended. Then the recommendation of the algorithm was compared with the suggestion of an expert specializing in the treatment of glaucoma. Results. The proposed innovative algorithm for treating POAG patients sets up four stages in the appointment of topical hypotensive therapy. When gaining a certain number of points, the algorithm recommends surgical treatment. The treatment tactics suggested by the algorithm, agreed with the opinion of glaucoma expert in most of the cases (27 out of 30 cases; 90%). Conclusion. An algorithm for the treatment of patients with POAG has been proposed and tested. The algorithm makes it possible to assess the progression of the glaucomatous process and select the optimal tactics for managing the patient in real time of examination.